The introduction of islamic sharia bonds on an investment instruments (Increasing the capacity of devotion to the community) - Evan Stiawan; Faisal Muttaqin (Yayasan Darussalam Bengkulu, 2025)
The growth of Sukuk in Indonesia is still quite low compared to other countries with a majority Muslim population. It is still urgent for the academy to analyze the growth of sukuk in regions in Indonesia and to find out what strategies are for developing sukuk in the future. Meanwhile, the development of sharia investment in Bengkulu province in 2019 has increasingly shown its development. The main source of income for the people of Kaur Regency comes from coffee, palm oil, rubber, and rice field plantations. The investments that have been made so far are only investments in deposits, house purchases, and plantation land. Meanwhile, investment through sukuk is still unfamiliar among the people of Kaur Regency. The objectives to be achieved from the introduction of this sukuk are to find out how the people of Bengkulu City understand the sukuk instruments in the sharia capital market. To analyze whether sukuk instruments can act as an investment vehicle that can help the government build the country, especially Bengkulu province. The research approach used in this study is the PAR method or Participatory Action Research. Participatory Action Research is a research model that seeks something to connect the research process to the process of social change. The purpose of the sharia investment teaching program or State Sharia Securities in Rural Communities is that the Indonesian people will benefit from sukuk issued by the Indonesian government, produce reference materials for teaching materials, as a means to redevelop investment with sukuk instruments as a means to build the country and as input and consideration for the government in developing sharia investment in sukuk instruments in communities in the regions